Historicity of Early Islamic Tafsir; Study the Sources, Characteristics and Methods of Companion's Interpretation: (Historisitas Tafsir Masa Awal Islam; Telaah Sumber, Karakteristik, dan Metode Tafsir Sahabat) - Yurid Shifan Alal Firdaus; S Sumarkan; Nur Istiqlaliyah (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
The historiy of Qur’anic interpretation in the early days of Islam has its own characteristics, one of which is the interpretation of the Companions era. Central figures in the development of tafsir during the Sahabat era, such as Abdullah bin Abbas, Abdullah bin Mas'ud, and Ubay bin Ka'ab, had a significant influence on the treasures of Islamic scholarship. This article focuses on examining the sources, characteristics and methods of interpretation used by the Sahabat to reveal the deepest meaning and message of the Qur’an. The research model used is a qualitative model, library research type, and applies descriptive-analytical methods. The final results of the discussion in this article include, first, the sources of interpretation of friends consisting of the Qur’an, hadith of the Prophet, ijtihad friends, and information from book experts (israiliyyat). Second, the characteristics of the interpretations of the Sahabat era have similarities with the interpretations of the Prophet's era, while the difference lies in the source and quality of the interpretation. Third, the method of interpretation used by the Sahabat is the interpretation of histories that are elaborated globally.